PENGARUH GREEN PRODUCT, GREEN PRICE DAN GREEN PLACE TERHADAP KEPUTUSAN PEMBELIAN - Tanamas, Randy Reliantama; Pratiwi, Caecilia Widi; Suwardi, Suwardi (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
The purpose of this study is to analyze the influence of green product, green price, and green place on the purchasing decision of Fore Coffee at Taman Galaxy Bekasi, both partially and simultaneously. The data collection method used in this study involves primary data and the use of questionnaires. The population in this study consists of respondents aged at least 17 years who have purchased Fore Coffee at Taman Galaxy. The sample in this study includes 100 respondents. The sampling method used is non-probability sampling with a purposive sampling technique. The testing stages conducted include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, partial test (t-test), simultaneous test (f-test), and coefficient of determination test. The testing tool used is SPSS version 25. The results of this study indicate that the green price variable does not have a partial effect on purchase decisions, while the green product and green place variables do have a partial effect on purchase decisions. However, the green product, green price, and green place variables jointly (simultaneously) have an effect on purchase decisions.